Combinations of Anticyclic Citrullinated Protein Antibody, Rheumatoid Factor, and Serum Calprotectin Positivity Are Associated With the Diagnosis of Rheumatoid Arthritis Within 3 Years. Issue 10 (20th July 2021) - Bettner, Leah F.; Peterson, Ryan A.; Bergstedt, Dylan T.; Kelmenson, Lindsay B.; Demoruelle, M. Kristen; Mikuls, Ted R.; Edison, Jess D.; Parish, Mark C.; Feser, Marie L.; Frazer‐Abel, Ashley A.; Moss, Laura K.; Mahler, Michael; et al.
Abstract : Objective: To evaluate the prevalence of elevations of anti‐cyclic citrullinated peptide‐3 (anti‐CCP3) antibody, rheumatoid factor IgM (RF‐IgM) and serum calprotectin (sCP) in pre–rheumatoid arthritis (RA) as well as the diagnostic accuracies of these biomarkers for the timing of diagnosis of future RA. Methods: A total of 215 RA cases, each with approximately three pre‐RA diagnoses and one post–RA diagnosis serum sample, and controls were identified from the Department of Defense Serum Repository. All case samples and a single sample from each control subject were tested for anti‐CCP3 (IgG), RF‐IgM, and sCP. The diagnostic accuracies of biomarkers for future RA were evaluated. Results: Anti‐CCP3, RF‐IgM, and sCP were elevated in pre‐RA, with anti‐CCP3 and sCP significantly elevated compared with RF‐IgM at the earliest time points. Within the cases, the combination of anti‐CCP3 and RF‐IgM positivity had a positive predictive value (PPV) of 35.6% for a diagnosis of RA in 3 years or less, which is significantly higher than the PPV of 18.7% for anti‐CCP3 positivity alone ( P < 0.001). A combination of anti‐CCP3, RF‐IgM, and sCP had the highest PPV (53.0%) for a diagnosis of RA in 3 years or less; however, this was not significantly higher than the PPV for anti‐CCP3 and RF‐IgM positivity ( P = 0.248). Conclusion: Anti‐CCP3, RF‐IgM, and sCP are elevated in pre‐RA; furthermore, combinations of elevations of these biomarkers are more commonly seen in the period of less than or equal to 3 years to diagnosis. This may be considered in creating inclusion criteria in prevention trials in RA. In addition, the biologic relationships of these biomarkers in pre‐RA need exploration.